STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MENUMBUHKAN MINAT BELAJAR MENGHAFAL JUZ AMMA SISWA KELAS VIII A SMPN 10 TELUK KERAMAT - Melia Nur Risqie; Purniadi Putra, Sera Yuliantini (ADISAM PUBLISHER, 2025)
The objective of this research is to explore: 1) The implementation of strategies by Islamic Religious Education teachers in cultivating students' interest in memorizing Juz A’mma among eighth-grade students of SMPN 10 Teluk Keramat; 2) Fostering students' interest in memorizing Juz A’mma among eighth-grade students of SMPN 10 Teluk Keramat. This study adopts a qualitative approach with a phenomenological research design. Data collection methods include interviews, observations, and documentation. Data analysis involves data reduction, presentation, verification, and conclusion drawing. Data validity is ensured through triangulation and member checks. The findings reveal: 1) The implementation of strategies by Islamic Religious Education teachers in memorizing Juz A’mma, specifically targeting eighth-grade students. Students are required to memorize a minimum of 12 chapters annually as a prerequisite for final grades/report cards, utilizing memorization, talqin (repetition), talaqqi (listening to recitations), and tikrar (repetition) strategies, and preselecting the chapters to be memorized. 2) Fostering students' interest in memorizing Juz A’mma among eighth-grade students of SMPN 10 Teluk Keramat involves providing motivation, elucidating the benefits and virtues of reading the Quran, rewarding extensively memorized students with high grades, continually monitoring their memorization progress, and incorporating Quranic literacy techniques before and after learning